Preparation and electrochemical characterization of Ti‐based amorphous metallic glass with high strength. Issue 5 (20th November 2020) - Li, Xuewu; Zhang, Lin; Shi, Tian; Yu, Weining; Shao, Jinhui; Zhou, Xuegang; He, Yuxing; Zhang, Binbin
Abstract: Ti‐based amorphous metallic glasses have excellent mechanical, physical, and chemical properties, which is an important development direction and research hotspot of metal composite reinforcement. As a stable, simple, efficient, and large‐scale preparation technology of metallic powders, the gas atomization process provides an effective way of preparing amorphous metallic glasses. In this study, the controllable fabrication of a Ti‐based amorphous powder, with high efficiency, has been realized by using gas atomization. The scanning electron microscope, energy‐dispersive spectrometer, and X‐ray diffraction are used to analyze surface morphology, element distribution, and phase structure, respectively. A microhardness tester is used to measure the mechanical property. An electrochemical workstation is used to characterize corrosion behavior. The results show that as‐prepared microparticles are more uniform and exhibit good amorphous characteristics. The mechanical test shows that the hardness of amorphous powder is significantly increased as compared with that before preparation, which has the prospect of being an important part of engineering reinforced materials. Further electrochemical measurement shows that the corrosion resistance of the as‐prepared sample is also significantly improved. This study has laid a solid foundation for expanding applications of Ti‐based metallic glasses, especially in heavy‐duty and corrosive domains. Abstract : A Ti‐based amorphous powder with uniform distribution has been achieved by gas atomization. The hardness of such amorphous metallic glass is significantly increased, thus showing a broad prospect for being an important part of engineering reinforced materials. The further electrochemical measurement indicates that as‐prepared material also possesses visibly enhanced corrosion resistance.